Experiences of cancer survivors in Europe: Has anything changed? Can artificial intelligence offer a solution? - Hesso, Iman; Kayyali, Reem; Charalambous, Andreas; Lavdaniti, Maria; Stalika, Evaggelia; Lelegianni, Maria; Nabhani-Gebara, Shereen (My University, 2022)
Cancer is a major global health issue. Despite technological advancements in oncology, challenges remain in many aspects related to cancer management. This study constitutes one part of the user requirement definition of INCISIVE EU H2020 project, which has been designed to explore the full potential of artificial intelligence (AI) based technologies in cancer imaging. The study aimed to explore cancer survivors' experiences of cancer care in five European countries.
Keywords: Europe; Artificial intelligence; Cancer care; Cancer diagnosis; Cancer survivors; Cancer treatment; Experiences; Perceptions